Clinical findings in the renal victims of a catastrophic disaster: the Marmara earthquake - (:unkn) unknown (OXFORD UNIV PRESS, 2002)
Background. The clinical course of acute renal failure (ARF) related to crush syndrome is very complex, because of co-existing surgical and/or medical complications. After the devastating Marmara earthquake that struck Turkey in August 1999, 639 patients were identified with nephrological problems, whose clinical findings have been the subject of this analysis. Methods. Specific questionnaires asking about 63 variables were sent to 35 reference hospitals that treated the victims. Clinical findings of the renal victims were analysed. Results. At admission, high fever was noted in 31.8% of the patients; the temperature of non-survivors was higher (P = 0.027). Mean blood pressure was higher in survivors (P = 0.004) and dialysed victims (P < 0.001). Most (61.4%) patients were oligo-anuric; oliguria lasted for 10.8 +/- 7.2 days. Thoracic and abdominal traumas were associated with a higher risk of mortality. 397 fasciotomies and 121 amputations were performed in 790 traumatized extremities. Fasciotomies were associated with sepsis (P < 0.001) and dialysis needs (P < 0.0001), while amputations were associated with mortality (P < 0.0001). Medical complications, which were associated with dialysis needs (P < 0.0001) and mortality (P < 0.0001), were observed in 51.5% of patients. In a multivariate analysis model of medical complications, disseminated intravascular coagulation (DIC) (P < 0.0001, OR = 5.81), and adult respiratory distress syndrome (ARDS) (P = 0.0001, OR = 4.53) were predictors of mortality. Conclusions. In the aftermath of catastrophic earthquakes, clinical findings of the renal victims can predict the final outcome. While fasciotomies indicate dialysis needs, extremity amputations, abdominal and thoracic traumas are associated with higher rates of mortality in addition to DIC and ARDS.
Keywords: clinical features; crush syndrome; Marmara earthquake; HANSHIN-AWAJI-EARTHQUAKE; CRUSH-SYNDROME; RHABDOMYOLYSIS; FAILURE; INJURY